Maternal Serum Netrin-1 Levels in Pregnancies Complicated by Gestational Diabetes Mellitus - Colak, Busra; Kender Erturk, Nergis; Kartal Golcuk, Esra; Dincgez, Burcu; Erturk, Anil (The European Research Journal, 2026)
Objective: Gestational diabetes mellitus (GDM) is associated with metabolic and vascular disturbances, yet its underlying biological mechanisms remain incompletely understood. Netrin-1, a multifunctional protein involved in angiogenesis, inflammation, and endothelial homeostasis, has been implicated in metabolic disorders; however, clinical data in GDM are limited. This study aimed to evaluate maternal netrin-1 levels in pregnancies complicated by GDM and to assess their associations with clinical parameters.Methods: This prospective case–control study included 45 pregnant women with GDM and 80 healthy pregnant controls between 24 and 28 weeks of gestation. Serum netrin-1 concentrations were measured using enzyme-linked immunosorbent assay. Clinical characteristics, glycemic parameters, and pregnancy outcomes were recorded. Receiver operating characteristic (ROC) analysis assessed the discriminatory performance of netrin-1 for GDM, and correlation and multivariable regression analyses identified associations after adjustment for selected covariates.Results: Serum netrin-1 levels were significantly lower in GDM group compared with controls (P